Availability of Limited Service Food Outlets Surrounding Schools in British Columbia - Black, Jennifer L. (Can J Public Health, 2012)
OBJECTIVE: The purpose of this study was to provide a descriptive profile of the availability of limited service food outlets surrounding public schools in British Columbia, Canada. METHODS: Data from the 2010 Canadian Business Data Files were used to identify limited service food outlets including fast food outlets, beverage and snack food stores, delis and convenience stores. The number of food outlets within 800 metres of 1,392 public schools and the distance from schools to the nearest food outlets were assessed. Multivariate regression models examined the associations between food outlet availability and school-level characteristics. RESULTS: In 2010, over half of the public schools in BC (54%) were located within a 10–12 minute walk from at least one limited service food outlet. The median closest distance to a food outlet was just over 1 km (1016 m). Schools comprised of students living in densely populated urban neighbourhoods and neighbourhoods characterized by lower socio-economic status were more likely to have access to limited service food outlets within walking distance. After adjusting for school-level median family income and population density, larger schools had higher odds of exposure to food vendors compared to schools with fewer students. CONCLUSION: The availability of and proximity to limited service food outlets vary widely across schools in British Columbia and school-level characteristics are significantly associated with food outlet availability. Additional research is needed to understand how food environment exposures inside and surrounding schools impact students’ attitudes, food choices and dietary quality.